Selection parameters for improving the seed cotton yield and fibre quality traits in American Cotton (Gossypium hirsutum L.) - K. N. Ganesan and T. S. Raveendran (Electronic Journal of Plant Breeding, 2010)
Information on the influence of different yield components on improvement of yield will be crucial in any selectionprogramme. Four intra-hirsutum hybrids viz., TCH1452 x MCU5, TCH1628 x Gh493, TCH1628 x MCU5 and SVPR2 xMCU5 were developed by utilizing the five genetically diverse American cotton (Gossypium hirsutum L.) genotypes asparents. Observations were recorded on plant height, boll number, boll weight, ginning outturn, lint index, seed index, 2.5%span length, bundle strength, fibre fineness, elongation % and seed cotton yield in F2 population and correlation of yield andits components were analysed to understand the relative contribution of different yield components in enhancing the yieldand fibre quality. Study revealed significant positive association of plant height, sympodia, boll number, boll weight withyield. Span length had highly significant negative association with yield whereas uniformity ratio exhibited both positivelyand negatively significant association with yield. Associations of fibre fineness, fibre strength and elongation % with seedcotton yield was non-significant. Association of traits inter se revealed the positive association of plant height withsympodia, uniformity ratio, 2.5% span length and number of bolls, sympodia with uniformity ratio and boll number, bollweight with uniformity ratio, seed index with ginning %, fibre length with bundle strength, uniformity ratio with micronaireand elongation %. Significant negative correlation of bolls with fibre strength and 2.5% span length, lint index with 2.5%span length and ginning %, fibre length with uniformity ratio and elongation %, micronaire with fibre strength was observed.Information generated on the relationship between yield components, fibre quality and yield in F2 generation will help thecrop breeder in enhancing the efficiency of selection.